2013
DOI: 10.1115/1.4024589
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Loss Mechanisms and Identifying Areas of Improvement for HCCI Engines Using Detailed Exergy Analysis

Abstract: This paper presents a detailed exergy analysis of homogeneous charge compression ignition (HCCI) engines, including a crank-angle resolved breakdown of^ mixture exergy and exergy destruction. Exergy analysis is applied to a multizone HCCI simulation including detailed chemical kinetics. The HCCI simulation is validated against engine experiments for ethanol-fueled operation. The exergy analysis quantifies the relative importance of different loss mechanisms within HCCI engines over a range of engine operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The model highlights that these trends can be related to the different loss mechanisms in the engine. Prior studies suggested that partial combustion events and the heat lost to the walls are the main loss mechanisms. Model results show that in the operating conditions located in the middle of the operating map for PRF100 (lambda = 3, EGR = 30%), about 38% of the total heat from the combustion chamber is exchanged with the piston head, while 62% is lost to the cylinder walls and head. The relatively small contribution of cylinder walls is because the heat losses mainly take place at a Crank Angle Degree (CAD) close to the TDC, since the gas temperature is close to the maximum value.…”
Section: Fuel Effects On Hcci Operability Mapsmentioning
confidence: 97%
“…The model highlights that these trends can be related to the different loss mechanisms in the engine. Prior studies suggested that partial combustion events and the heat lost to the walls are the main loss mechanisms. Model results show that in the operating conditions located in the middle of the operating map for PRF100 (lambda = 3, EGR = 30%), about 38% of the total heat from the combustion chamber is exchanged with the piston head, while 62% is lost to the cylinder walls and head. The relatively small contribution of cylinder walls is because the heat losses mainly take place at a Crank Angle Degree (CAD) close to the TDC, since the gas temperature is close to the maximum value.…”
Section: Fuel Effects On Hcci Operability Mapsmentioning
confidence: 97%
“…Estudios relacionados con la cinética química en procesos que involucran sustancias combustibles que han sido estudiados por investigadores en Colombia Descripción Referencia Análisis teórico (S. Gómez et al, 2013) Técnicas ab initio (Calderón et al, 2015;Juan F. Espinal et al, 2004, 2007Jimenez-Orozco et al, 2018;A. Montoya et al, 2000;Alejandro Montoya et al, 2001, 2002a, 2002bPalacio et al, 2018;Sanchez et al, 2019;Vélez et al, 2009) Mecanismos para uso en combustión (Quiceno et al, 2002) Mecanismos para uso en equipos de craqueo de fracciones de petróleo (López-Pérez, 2016) Sistemas de combustión complejos (Alvarado et al, 2009;Amador et al, 2017;Burbano et al, 2011b;Cardona Vargas & Amell-Arrieta Andrés Adolfo Arrieta Carlos, 2016;Saxena et al, 2013;Yepes & Amell, 2013) Combustibles líquidos (Padilla et al, 2017b) Combustibles sólidos (Rojas et al, 2012) Tabla 9S. Investigaciones relacionadas con la combustión realizadas por investigadores colombianos Descripción Referencia Relación con características de Colombia: altura sobre el nivel del mar (presión atmosférica), humedad y composición química de combustibles en aplicaciones relacionadas con aplicaciones industriales de la combustión (Andrés A.…”
Section: Koreaunclassified
“…A commonly preferred methodology combining first and second laws of thermodynamics for evaluation of thermal systems is known as exergy analysis (Moran and Sciubba, 1994;Dincer and Cengel, 2001;Tsatsaronis, 2007). However, numerous papers on exergy analysis of different systems have been presented to the literature after appreciation of the exergy analysis (Zhang and Lior, 2004;Saxena et al, 2013;Zhao et al, 2016a;Zhao et al, 2016b;Akbulut et al, 2016;Cakici et al, 2017;Salpingidou et al, 2018;Caglayan and Caliskan, 2018;Calli et al, 2019;S öhret et al, 2019). Regarding working principle of aircraft gas turbine engines, performance evaluation of them in terms of exergy has always drawn attention of researchers (Arntz et al, 2015;S öhret et al, 2016;Hayes et al, 2017;Dong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%